PEMANFAATAN MINYAK ATSIRI KULIT BUAH HONJE SEBAGAI ANTIOKSIDAN PRODUK SOSIS AYAM - Dede Sukandar; Anna Muawanah; Tarso Rudiana; Khilda Fithri Aryani (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2017)
A study on the inhibition of oxidative deterioriation of chicken sausage products added with essential oil from honje (Etlingera elatior) fruit skin was conducted. The purpose of this study was to determine the antioxidative activity of essential oils of fruit peels of honje and its effect on the inhibition of oxidative deterioration of chicken sausage products. The antioxidant activity assay of the essential oils and chicken sausages added with 0, 50, 100, and 160 µg/mL essential oil was then analyzed. The best formula of chicken sausages was determined by organoleptic test, i.e.a hedonic test on untrained panelists and by the inhibition of oxidative deterioration measured as malondialdehyde content. In addition, analysis of moisture, ash, fat, protein, carbohydrate, metal contamination and microbial contamination of the sausages was also done. The results showed that the essential oil of the honje fruit skin had an antioxidant activity (IC50) of 21.296 mg/mL, and the best chicken sausages was those added with µg/mL essential oils. The characteristics of the best chicken sausages complied with SNI 01-3820-1995 sausage quality standard, with water content of 66.75% (w/w); ash content of 1.26% (w/w); fat content of 2.90% (w/w); protein content of 23.10% (w/w); carbohydrate content of 5.99% (w/w); Metal Zn 14.17 mg/kg; Cu 0.65 mg/kg; and no microbial contamination.